Evaluation of an online case study-based course in translational science for a broad scientific audience: Impacts on students' knowledge, attitudes, planned scientific activities, and career goals. Issue 1 (7th June 2022) - Vogel, Amanda L.; Hussain, Shadab F.; Faupel-Badger, Jessica M.
Abstract: Purpose: There is a need for education activities in translational science (TS) that focus on teaching key principles, concepts, and approaches to effectively overcome common scientific and operational bottlenecks in the translational process. Delivering this content to the broad range of individuals interested in advancing translation will help to both expand and develop the TS workforce. Rigorous evaluations will build the evidence base for effective educational approaches for varied audiences. Methods: In 2020, the National Center for Advancing Translational Sciences offered an online case study-based course in TS for students across education and career stages. The course evaluation used baseline and endpoint student surveys to assess satisfaction with the course and impacts of participation on knowledge and attitudes relevant to TS and professional goals. Results: Of 112 students, 100 completed baseline and/or endpoint surveys, with 66 completing both. Most found the online format ( n = 59, 83%) and case study approach ( n = 62, 87%) moderately or very effective. There were statistically significant increases in TS knowledge ( P < .001) and positive attitudes about team science in translational research (TR) ( P < .001). Students reported the course increased their skills and knowledge in cross-disciplinary team science, the process of preclinical and clinical TR, and how their work fits into the translational spectrum, and increased their interest in scientific approaches used in the case study and careers in TS, TR, or team science. Conclusions: This online case study-based course effectively conveyed TS concepts to students from a range of backgrounds and enhanced their professional interests related to course content.